Family empowerment to increase Covid-19 vaccination coverage for elderly in Bedoro Village, Sragen - Tri Susilowati; Erika Dewi Noorratri (Community Empowerment, 2023)
Data up to March 6 2021 show that 18,131 of the 37,154 COVID-19 patients who passed away in Indonesia were elderly. The findings of a preliminary study that involved interviewing 10 elderly residents of Sragen Regency revealed that the majority of the elderly claimed to be afraid and unaware of the advantages and risks of the Covid-19 vaccination. In order to increase vaccination coverage, this community service aims to increase residents' knowledge of the Covid-19 vaccination. Pre-tests, counseling sessions, and post-tests are all part of the implementation method. The outcome of this activity is an improvement in residents' knowledge. Residents' knowledge of the significance of the Covid-19 vaccination was only 15% in the good category prior to counseling and increased to 41% after counseling.